Online Thesis Exam Evaluation Using Zoom Cloud Meeting During the Covid-19 Pandemic - Nurcholish Arifin Handoyono; Suparmin Suparmin (VANOS Journal of Mechanical Engineering Education, 2020)
The research aims to obtain a description of: (1) supporting factors; and (2) Inhibiting factors for the online thesis exam using the zoom cloud meeting during the COVID-19 pandemic. This type of research is an evaluation using the CIPP model (Context, Input, Process, and Product). The research subjects were students of the study program of PVTM FKIP UST who had conducted an online thesis examination consisting of 28 students. Data collection techniques used questionnaires, interviews, and documentation. The data analysis technique used an average analysis which was assessed based on the assessment category. The results showed that: (1) The supporting factors for the online thesis examination using Zoom Cloud Meeting were: (a) The context aspect of 3.22 was categorized as high; (b) the input aspect of 3.16 is categorized as high; (c) the process aspect of 3.04 is categorized as high; and (d) the product aspect is 3.42 which is categorized as very high; and (2) factors inhibiting the online thesis exam using Zoom Cloud Meeting, namely: (a) Weak internet connection; (b) There are obstacles during the examination process; and (c) Inefficient examination time